The Effect of Marketing Agility in Reducing Marketing Risk (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The study aims to diagnose the nature of the relationship and the impact between marketing agility and marketing risk, as studies have confirmed that marketing agility is one of the most important factors that enable organizations to adapt to the environment and its variables, and enable the organization to make its marketing decisions quickly and implement them with high flexibility, in a way that enables it to avoid or reduce Marketing risk to the maximum extent possible, Scientific Bureau and Drug Store were selected as a field for study, and their employees were selected as a sample for the study, which numbered (311) respondents, and with the aim of collecting the required data and information, the questionnaire was designed as a main tool in data collection, which was covered through (66) phrases. Included in the questionnaire based on a group of scientific sources, the study adopted the descriptive analytical approach in an attempt to answer the questions of the study and test its hypotheses using Structural Equation Modeling (SEM). The moral effect of marketing agility in reducing marketing risk, as well as the results of the analysis that led to the mechanism of testing the correlation and impact relationships confirms that the harmonization between the dimensions of marketing agility contributes to supporting the trends of the researched organizations in reducing the marketing risk